Modeling the internet congestion control as a time delay system: A robust stability analysis - Saverio Mascolo (IFAC Proceedings Volumes, 2003)
In this paper control theoretic analysis is employed to model the Internet flow and congestion control as a time delay system. It is shown that the self-clocking principle, which is known to be a key component of the Transmission Control Protocol (TCP), corresponds to implement a simple proportional controller (P) plus a Smith predictor (SP). It is also shown that different variants of the TCP congestion control algorithms, such as classic TCP Reno or the recent Westwood TCP, can be modelled by proper input shaping of the reference signal. Finally, the robustness of the control algorithm in the face of uncertain round trip time delay is analysed.
4th IFAC Workshop on Time Delay Systems (TDS 2003), Rocquencourt, France, 8-10 September 2003
Keywords: Telecommunication; Internet; Time-delay systems